2005
DOI: 10.1074/jbc.m504087200
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine-scanning Mutagenesis of Serotonin Transporter Intracellular Loop 2 Suggests an α-Helical Conformation

Abstract: The serotonin transporter (SERT, 1 SLC6A4) is a presynaptic plasma membrane protein responsible for the reuptake of serotonin (5-hydroxytrypatamine, abbreviated 5-HT) after its release by neurons. It is a member of a large family of amine and amino acid transporters (SLC6, NSS) distributed throughout the prokaryotic and animal kingdoms. Together with norepinephrine and dopamine transporters (NET and DAT), SERT is part of a subgroup of transporters that mediate the transport of biogenic amine neurotransmitters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 30 publications
3
64
0
Order By: Relevance
“…Another and more likely explanation is that Thr-258 and Ser-259 only might be exposed in certain conformation during the transport cycle and/or to allow phosphorylation in the milieu of the lipid-mobile phase of mammalian plasma membrane; hence, the LeuT structure only represents a single snapshot of a highly dynamic protein in which both the putative extracellular and intracellular gates are closed. Interestingly, a recent study using cysteinescanning mutagenesis showed that in SERT, the region between TMD4 and TMD5 encompassing Thr-276 and Ser-277 (Thr-258 and Ser-259 in NET) is accessible from the cytoplasmic side to cysteine-reactive reagents suggesting that ICL2 is much longer than the initially predicted sequence, at least in certain conformations (59).…”
Section: Discussionmentioning
confidence: 99%
“…Another and more likely explanation is that Thr-258 and Ser-259 only might be exposed in certain conformation during the transport cycle and/or to allow phosphorylation in the milieu of the lipid-mobile phase of mammalian plasma membrane; hence, the LeuT structure only represents a single snapshot of a highly dynamic protein in which both the putative extracellular and intracellular gates are closed. Interestingly, a recent study using cysteinescanning mutagenesis showed that in SERT, the region between TMD4 and TMD5 encompassing Thr-276 and Ser-277 (Thr-258 and Ser-259 in NET) is accessible from the cytoplasmic side to cysteine-reactive reagents suggesting that ICL2 is much longer than the initially predicted sequence, at least in certain conformations (59).…”
Section: Discussionmentioning
confidence: 99%
“…43. Binding to membranes was measured before and after incubation with MTSEA or MTSES (19), and typical results are shown in Fig. S1.…”
Section: Mts Reactivity Measurementsmentioning
confidence: 99%
“…19. Each mutant was tested for transport activity and sensitivity to MTS reagents by transfecting HeLa cells with plasmids bearing each mutant cDNA under control of a T7 promoter and infecting with vTF7-3, a recombinant vaccinia virus expressing bacteriophage T7 RNA polymerase (42).…”
Section: Mts Reactivity Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…All mutants were sequenced to verify the accuracy of the procedure. Transport measurements were performed as described (37). Briefly, HeLa cells transfected with SERT mutant DNA using the vaccinia T7 system (38) were grown in 24-or 48-well plates, rinsed into medium containing [ 3 H]5-HT and the indicated Cl Ϫ concentration, incubated 10 min at 25°C, rinsed again, and counted.…”
Section: Calculation Of Electrostatic Interaction Energiesmentioning
confidence: 99%